The Impact of Socio-Economic Status on Teachers' Performance in SMP Negeri 2 Parigi Gowa Regency - Jalal; Hasanudin Kasim; Akhiruddin; Muh Reski Salemuddin; Sriwahyuni; Hasanuddin (CV. Eureka Murakabi Abadi, 2023)
This study aimed to determine the impact of socio-economic status on the performance at SMP Negeri 2 Parigi, Gowa Regency. This study uses a correlational with a quantitative approach. The population in this study was SMP Negeri 2 Parigi teachers in Gowa Regency, totaling 18 teachers, Collection technique data by questionnaire. Data processing techniques using SPSS t test, namely for looking for a correlation between the variables X and Y. In calculating the hypothesis obtained value Sig 0.031. Data collection techniques through questionnaires. These results indicate that the Sig value is less than 0.05 (0.031 less than 0.05). This means that the hypothesis proposed by the researcher is accepted, namely there is positive and significant influence in the study entitled